Masculinization of populations reverses sex differences in fertility - Henrik-Alexander Schubert; Thomas Spoorenberg; Christian Dudel; Vegard Fykse Skirbekk (Proceedings of the National Academy of Sciences, 2026)
Reproductive-age populations show a growing male surplus around the globe as a consequence of declining mortality, narrowing sex differences in mortality, and sex-selective abortions in some countries. Population structures are important determinants of marriage markets and childbearing. In this study, we estimate the past, current, and future difference between the male and the female total fertility rates around the world using an established indirect demographic approach drawing on data from the UN World Population Prospects. Our results indicate a crossover from historically higher male fertility to increasingly higher female fertility, which occurs globally in 2024. This shift is not toward parity, but rather reflects a growing disparity driven by the increasing male surplus at reproductive ages, which exerts downward pressure on male fertility rates relative to those of women. The difference is expected to grow to up to 20% in countries like China and India, where sex-selective abortion has reinforced sex imbalances in population structures. Overall, we highlight the growing sex inequalities in reproduction and call for more research on sex differences in fertility.